CONJUGATION PROBLEM WITH INTEGRAL CONDITION WITH RESPECT TO TIME FOR MIXED PARABOLIC- HYPERBOLIC TYPE EQUATION - Савка, Іван Ярославович; Симотюк, Михайло Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The conditions of correctness in Sobolev spaces to the conjugation problem with integral condition for parabolic-hyperbolic equations in cylindrical domain (− α , β ) × ( R p /2 π Z p ) are established.